Description of Nutritional Status and Diet of Mothers in Families at Risk of Stunting - Cahyani, Putri; Effendy, Devi Savitri (Universitas Mandala Waluya, 2024)
The stunting prevalence in Southeast Sulawesi reached 27.7% in 2022, and 21.5% of children were stunted in 2023, based on the Indonesian health survey. Reducing stunting requires targeted assistance to families at risk, including pregnant women, nursing mothers, and children aged 0-59 months. This study aimed to assess mothers' nutritional status and dietary patterns in families at risk of stunting in Punggaloba and Dapu-Dapura Villages, West Kendari District, Kendari City, in 2024. Using an observational descriptive survey, 110 mothers were selected through random sampling. The results revealed that 2.7% of participants were undernourished, 69.1% had normal nutritional status, and 28.2% were obese. While 71.8% demonstrated good meal frequency, dietary quality was generally poor, marked by insufficient macro- and micronutrient intake, and 65.5% lacked dietary diversity. Nutritional status was categorized as usual, but dietary patterns remained suboptimal. Improved dietary practices are recommended to meet nutritional needs effectively.